2018
DOI: 10.17221/81/2018-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Selected blood biochemical indicators of Cherry Valley ducks undergoing fattening in relation to their diet and sex

Abstract: The aim of the present study was to assess dietary and sex-related effects on selected blood indicators of 40-day-old mallard ducks undergoing fattening. The ducks were divided into three dietary groups (control, L50 and L100). The control (C) group was fed a diet containing soybean meal as the main protein component of the feed. In both experimental groups L50 and L100 soybean meal was replaced with meal of whole seeds of white lupine, Zulika variety, in proportions of 50 and 100%, respectively. With respect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 48 publications
4
5
1
Order By: Relevance
“…The positive effect of lupin protein on production and health was not apparent only in hens and chickens. Similar findings were reported by Jerabek et al (2018), who confirmed the effect of feeding diet containing lupin on lower levels of cholesterol and triacylglyceride values in the blood plasma of fattened ducks. Feeding diet with lupin to turkeys, positively reflected the development and function of their gastrointestinal tract and also the absorption of nutrients from the feed which is closely linked with better production parameters (Zdunczyk et al 2016).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The positive effect of lupin protein on production and health was not apparent only in hens and chickens. Similar findings were reported by Jerabek et al (2018), who confirmed the effect of feeding diet containing lupin on lower levels of cholesterol and triacylglyceride values in the blood plasma of fattened ducks. Feeding diet with lupin to turkeys, positively reflected the development and function of their gastrointestinal tract and also the absorption of nutrients from the feed which is closely linked with better production parameters (Zdunczyk et al 2016).…”
Section: Discussionsupporting
confidence: 90%
“…The lupin meal in the diet did not affect the alanine aminotransferase (AST) activity in the blood plasma of the experimental groups which is positive because higher values of AST are sign of hepatic disorders. Even though, the mean AST values in the plasma of the hens were higher than values in the study of Jerabek et al (2018). This slight increase cannot be considered as harmful for the health of the layers because the values were still in physiological range and the difference may also have reason in variation of biochemical parameters between hens and ducks.…”
Section: Discussioncontrasting
confidence: 55%
“…Legume seeds are a valuable protein-rich feed material, and they reportedly have a positive effect on performance parameters [30,31]. In the present study, the body weights of the ducks were higher than those in feeding trials by Jerabek et al [32], who investigated the effects of a duck diet containing SBM and yellow lupin at levels of 50% and 100% of the feed ration. Olver [33,34] reported lower performance parameters in ducks fed a diet based on bitter lupin, which may be attributed to the negative effect of alkaloids.…”
Section: Discussionmentioning
confidence: 44%
“…Olver (1997) as well as Olver and Jonker (1998) concluded that 20% to 40% inclusion of lupin reduced the content of fat in 6-week-old ducks. In a study by Jerabek et al (2018), ducks fed a diet with 50% and 100% inclusion of YL as a replacement of SBM had lower BW compared to birds fed SBM. Our study did not reveal a significant effect of dietary lupin on BW and other carcass traits of birds.…”
Section: Discussionmentioning
confidence: 97%